Optical characterization and polaron radius of Bi2O3 doped silica borotellurite glasses - Geidam, I. G.; Matori, K. A.; M. K., Halimah; Chan, K. T.; Muhammad, F. D.; Ishak, M.; Umar, S. A.; Hamza, A. M. (Elsevier BV, 2022)
A system of silica borotellurite glasses containing bismuth oxide (Bi2O3) with empirical chemical relation [{(TeO2)0.7(B2O3)0.3}0.8(SiO2)0.2]1− x(Bi2O3)x (where x = 0.01–0.05 M fraction in step of 0.01) were synthesized via melt-quenching procedure. Density and molar volume, XRD, FTIR and UV–Vis spectroscopies were employed to examine some parameters related to physical, structural and optical properties of the glasses. The density, polaron radius, molar volume, oxygen packing density (OPD), oxygen molar volume and number of bonds per unit volume of the glasses were computed and discussed. The XRD and FTIR characterization results were presented and discussed accordingly. Via the obtained optical absorption and density/molar volume data, the band gap energy, Urbach energy, index of refraction, coefficient of optical transmission, metallization criterion (MC) and reflection loss were studied. The index of refraction, metallization criterion, coefficient of optical transmission and reflection loss range from 3.013 to 2.622, 0.271–0.338, 0.598–0.667 and 0.252–0.201 respectively. The values of Polaron radius range from 3.949 to 4.300 g cm− 3,73.009–72.297 g atm l− 1 and 6.943–4.092 Å respectively. The obtained values of the polaron radius are termed small polarons because they are within the lattice constants of each of the constituent oxides in the BSBT glasses. The MC values of the glasses are consistent with MC of non-metallic glasses as well as new nonlinear optical materials. High values of density, index of refraction and the value range of the metallization criterion suggest that the TeO2–B2O3–SiO2–Bi2O3 glasses are suitable for optoelectronic, nonlinear optical devices and radiation attenuation windows.